Sosialisasi Pengelolaan Limbah Dapur Serta Program 3R (Reuse, Reduce, Recycle) Bagi Pemilik Rumah Makan dan Jasa Boga di Wilayah Kota Tasikmalaya - Melly Mellyanawaty; Estin Nofiyanti; A Ibrahim; N Salman; N Nurjanah; N Mariam (LPPM Universitas Muhammadiyah Tasikmalaya, 2018)
Society services activity in kitchen waste management system has been implemented to the owner of restaurant and catering work in Tasikmalaya City area. This activity has colaborated with Indonesian Catering Associations (APJI). The rapid growth of restaurant and catering activities has created serious problems of energy requirement, water, and solid waste disposal. Less information and limited area become the problems in handling of kitchen waste. A simple technique is needed to overcome the environmental problem which is caused by kitchen waste. The components of kitchen waste include vegetables, peelings, fruit skins, spoilt fruit, cooked and uncooked meat, bones, fats, egg-shells, bread and pastries, cooked food waste, etc. Due to a high organic content, bioconversion technologies such as anaerobic digestion are more suitable to handle the waste convert to biogas. It would be reducing the LPG usage. For the kitchen wastewater, grease trap as pre-treatment followed by a physical and biological process is one of a simple process which can produce the effluent in accordance with government standard. The activities were continued by the socialization of 3R program (reuse, reduce, recycle) by doing demo utilization of kitchen solid waste such as packing material, mineral water bottle is made a handicraft. Knowledge transfer run well and the enthusiasm of the participants in following the activity were very good.